Eksplorasi Ruh, Nafs, Qalbu, dan Fitrah sebagai Potensi Dasar dalam Membentuk Kepribadian sebagai ‘Abdullāh - Khoirin, Taufiq; Fathin, Muhammad; Rohimah, Siti (Lembaga Yasin AlSys, 2025)
This study aims to explore the foundational potentials of the human being from the perspective of Islamic psychology, encompassing ruh, nafs, qalbu, and fitrah as the core components in shaping an Islamic personality. These four elements interact to form an integrated spiritual-psychological system: ruh serves as the source of divine values, fitrah as the natural inclination toward truth, qalbu as the moral center and spiritual compass, and nafs as a dynamic entity that undergoes transformation through the process of inner purification. Employing a qualitative approach based on library research, this study formulates an integrative model that places tazkiyah al-nafs (soul purification) as the central mechanism for harmonizing these four potentials in forming the identity of ‘Abdullah—a person wholly submissive to Allah. The findings demonstrate that a systematic synergy among ruh, nafs, qalbu, and fitrah is capable of cultivating a balanced and purposeful spiritual character. This conceptual framework contributes to the development of Islamic personality models and offers practical implications for character education, counseling, and personal development grounded in Islamic values.